Evaluation of Medication Use in Patients with Gastroesophageal Reflux Disease (GERD) in the Inpatient Unit at a Hospital in Cimahi - Syarifuddin, Syarifuddin; Septiani, Vina; Khoirunnisa, Syifa; Kristian, Randi; Vikasari, Suci Nar (Journal of Midwifery and Nursing, 2025)
Gastroesophageal Reflux Disease (GERD) is a pathological condition characterized by the regurgitation of gastric contents into the esophagus, resulting in symptoms affecting both the esophagus and extra-esophageal regions. The aim of this study is to ascertain the usage pattern and rationality of GERD medication consumption. This study utilizes an observational approach with a descriptive cross-sectional design. The data collection was performed retrospectively by examining the treatment histories of GERD patients documented in the medical records at the Inpatient Installation of Dustira Hospital from January to June 2023. The sample comprised 200 persons who met the inclusion criteria. Research indicated that individuals with GERD were predominantly female, comprising 73.5%, while males constituted approximately 26.5%. The predominant age range was 18-45 years, comprising 63.5%, followed by 46-59 years at 23.5%. 61 patients received a combination of omeprazole and sucralfate as the predominant medication. The analysis showed that 100% of patients utilized the medication with the appropriate indication, 97.5% with accurate drug selection, 100% with precise dosage, 100% with the right method of administration, and 100% with the appropriate administration interval